Feminist metaphors and philosophy (2008)
Abstract: In this study the author is concerned with the relation between philosophy and metaphors, and on the contribution of feminist philosophy to the ongoing discussion about the status of metaphors in philosophical discourse. She gives a concise discussion of the authors who are responsible for the current understanding of relationships of metaphor and philosophy. The main part of the study is made up of an analysis of the views of feminist philosophers on the role of metaphor in the philosophical texts of the classic authors, especially the metaphors of maleness and femaleness (G. Lloyd, E.F. Kittay, M. Le Doeuff ), and on the possibility of their reinterpretation. As an example of attempts at the philosophical exploitation of metaphors, the author analyses the metaphor of pregnancy in J. Kristeva, the metaphor of the depth of the sea in L. Irigaray, and the metaphor of the theatrical play in E. Buker. The author regards metaphors as an inseparable part of philosophical discourse and states that active philosophical (feminist) reinterpretations of metaphors are possible.